Constitutional conflict and the role of the National People’s Congress - Wang, Z (Foundation for Law, Justice and Society, 2008)
Constitutional disputes are unique among social disputes, given that the constitutionality or legality of laws (acts) and government actions is contested, and to solve them requires particular institutions and procedures. China revised its legal system, including criminal, civil, and administrative litigation procedures, after the Cultural Revolution in the late 1970's and promised to establish a socialist rule of law through the 1999 constitutional amendments. However, China was slow to develop a sound constitutional review mechanism, which meant that constitutional law did not form part of the common conception of rule of law.